2011
DOI: 10.1016/j.atmosenv.2011.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Can commonly-used fan-driven air cleaning technologies improve indoor air quality? A literature review

Abstract: a b s t r a c tAir cleaning techniques have been applied worldwide with the goal of improving indoor air quality. The effectiveness of applying these techniques varies widely, and pollutant removal efficiency is usually determined in controlled laboratory environments which may not be realized in practice. Some air cleaners are largely ineffective, and some produce harmful by-products. To summarize what is known regarding the effectiveness of fan-driven air cleaning technologies, a state-of-the-art review of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
138
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(143 citation statements)
references
References 58 publications
(29 reference statements)
1
138
0
4
Order By: Relevance
“…The pollutant removal ability of the air cleaners should preferably be quantified in terms of the Clean Air Delivery Rate (CADR) for easy comparison (Shaughnessy and Sextro 2006;Zhang et al 2011). For the removal of particles, which is the focus of this study, CADR has been reported by some studies (Offermann et al 1985;Batterman et al 2005;Waring et al 2008;Mang et al 2009;Agrawal et al 2010;Sultan et al 2011;Zuraimi et al 2011;Kim et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pollutant removal ability of the air cleaners should preferably be quantified in terms of the Clean Air Delivery Rate (CADR) for easy comparison (Shaughnessy and Sextro 2006;Zhang et al 2011). For the removal of particles, which is the focus of this study, CADR has been reported by some studies (Offermann et al 1985;Batterman et al 2005;Waring et al 2008;Mang et al 2009;Agrawal et al 2010;Sultan et al 2011;Zuraimi et al 2011;Kim et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Another way of removing pollutants is indoor air cleaning. Portable air cleaners for home and office usage utilize various techniques depending on which pollutants they target (Zhang et al 2011). No air cleaner removes all pollutants, and some even produce harmful by-products, such as ozone (Niu et al 2001;Britigan et al 2006;Waring et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…İç hava kalitesi, hasta bina sendromuna etki eden en önemli faktörlerdendir. Hava temizleme amacına yönelik olarak beş temel sistemin kullanıldığı görülmektedir [10].…”
Section: Bina Faktörleriunclassified
“…Her kirletici tipinin kendine özgü yapısından kaynaklanan farklı zararları olmakla birlikte en yaygın görülen sağlık etkileri; konjuktival tahriş, burun ve boğazda tahriş; baş ağrısı, deride alerjik reaksiyonlar, nefes darlığı, koordinasyon kaybı, bulantı; burun kanaması, yorgunluk, halsizlik, akciğer, böbrek ve merkezi sinir sisteminde hasardır. Bazı organik maddeler hayvanlarda, bazı maddeler de insanlarda kansere neden olabilmektedir [8,9,10].…”
Section: Introductionunclassified
“…Current advances in building management significantly impede IAQ improvement by the first two methods (Bennett, 2009), hence the option of pollution abatement is receiving more attention. Several technologies are available and already operational to this end, such as filter systems (Batterman et al, 2005;Bekö et al, 2008;Zhang et al, 2011), ozone generators (Kwong et al, 2008;Zhang et al, 2011) and plasma catalytic systems (Van Durme et al, 2007;Van Wesenbeeck et al, 2013).…”
Section: Introductionmentioning
confidence: 99%